Pengaruh Model Problem Based Learning dengan Pendekatan Multirepresentasi terhadap Hasil Belajar Siswa pada Materi Usaha dan Energi - Elysabeth Joseph Mangngella; Yusuf Kendek (Jurnal Kreatif Online, 2021)
This study aims to determine the effect of the problem-based learning model with a multi-representation approach on student learning outcomes on work and energy. The type of research used is an experimental design with "the equivalent pretest-posttest design". The sample was selected using purposive sampling technique and resulted in class XI IPA 1 (n = 30 students) as the control class and class XI IPA 2 (n = 30 students) as the control class. experimental class. The instrument used is a test of learning outcomes in the form of multiple choice. Based on the results of data processing, the average posttest score of the control class students' learning outcomes was 11.44. While the experimental class obtained the average posttest score was 14.90. Analysis of the test data was carried out using a two-party t-test statistical technique to test the difference in the mean scores of student learning outcomes with a significant level of =0.05. The results obtained are tcount = 0.09 and ttable = 2.00. This means that there is an effect of the problem based learning model with a multi-representation approach on student learning outcomes on business and energy materials at SMA Negeri 8 Palu.